Bibliometric mapping of digital storytelling research in English language education (Scopus, 2019-2024) - Alfiyatus Sa'adah; Zuliati Rohmah (JOALL (Journal of Applied Linguistics and Literature), 2026)
This purpose of the study is to visualize the research   field of of Digital Storytelling (DST) in the context of English Language Education (EFL and ESL) employing bibliometric methodology. In total, 127 peer-reviewed articles indexed in the Scopus database and published between 2019 and 2024. Articles have been identified via systematic searching in a database, subsequent removal of duplicate records and title/abstract screening for topical relevancy. The analysis of the dataset has been carried out using Biblioshiny, an analytical tool of Bibliometrix package in R software. Publication trends, prolific researchers, affiliations, countries, collaboration trends, citation metrics and thematic analysis were investigated via analyzing keyword co-occurrences and clustering. The results indicate that research into the topic grows in numbers, and the number of DST related publication tends to be high in Asian regions, particularly China, Hong Kong, and Indonesia with little collaboration between national DST scholars from other regions. Concerning themes, current researches tend to explore learner-focused approaches to learning, e-learning environments, and multimedia-supported English language instruction, leaving issues of under resourced settings and sustained impact untouched. Overall, the study provides a mapping of DST related research within the scope of English Language Education, this study highlights research concentrations and gaps that can inform future empirical investigations and support more context-sensitive and scalable applications of digital storytelling in English language teaching and learning.